The cold resistance of cottonseed during germination is related to the content of unsaturated fatty acids. Issue 5 (28th July 2021) - Chen, Ying; Tian, Liwen; Wan, Lu; Xia, Jun; Liu, Feng; Zhao, Ruihai; Wang, Tangang; Han, Chunli
Abstract: The agricultural industry is severely affected by low temperature due to its wide range of adverse effects. This work aimed to elucidate the changes in fatty acid composition during cotton ( Gossypium L.) seed germination and the relationship of that change and germination characteristics. Three temperatures, 15/12 (T12), 21/18 (T18), and 25/25 °C day/night (T25), were set to treat Xinluzao 65 (L65) and Xinhai 35 (H35). Under T12, the germination rate, germination index, and water absorption rate of the cotton seeds decreased, and the mean time of germination increased compared to T25. The germination rate, germination index and water absorption rate of H35 were 6.67, 5.15, and 17% higher, respectively, than those of L65 under the T2 treatment. The total lipids, saturated fatty acid/unsaturated fatty acid (SFA/UFA) ratio, and monounsaturated fatty acid/polyunsaturated fatty acid (MUFA/PUFA) ratio were 3.75, 0.30, and 4.98% higher, respectively, in H35 than in L65 under the T25 treatment. The water absorption rate of L65 was significantly positively correlated with C18:2 and significantly negatively correlated with C24:0 and C18:1. The water absorption rate and germination rate of H35 were significantly positively correlated with C14:0 and C16:1, and C18:2 was significantly negatively correlated with the germination rate and the water absorption rate. Therefore, low‐temperature stress in cotton results in an increase in the water absorption rate and consequent decreases in the concentrations of SFAs C20:0, C22:0, and C24:0, as well as an increase in the concentration of UFA C16:1. These changes enhance the ability of cotton seeds to resist cold damage. Core Ideas: Low temperature decreased the fatty acid content and germination ability of cotton seeds. The ratio of unsaturated/saturated fatty acid was correlated with cold resistance of cotton. Island cotton seed can resist low‐temperature stress better than upland cotton seed.